Ethyl methanesulfonate mutant library construction in Gossypium hirsutum L. for allotetraploid functional genomics and germplasm innovation. (28th April 2020) - Lian, Xin; Liu, Yan; Guo, Huihui; Fan, Yijie; Wu, Jianfei; Guo, Haixia; Jiao, Chengzhi; Tang, Zhengmin; Zhang, Li; Fan, Yupeng; Gou, Zhongyuan; Zhang, Changyu; et al.
SUMMARY: As the gene pool is exposed to both strain on land resources and a lack of diversity in elite allotetraploid cotton, the acquisition and identification of novel alleles has taken on epic importance in facilitating cotton genetic improvement and functional genomics research. Ethyl methanesulfonate (EMS) is an excellent mutagen that induces genome‐wide efficient mutations to activate the mutagenic potential of plants with many advantages. The present study established, determined and verified the experimental procedure suitable for EMS‐based mutant library construction as the general reference guide in allotetraploid upland cotton. This optimized method and procedure are efficient, and abundant EMS mutant libraries (approximately 12 000) in allotetraploid cotton were successfully obtained. More than 20 mutant phenotypes were observed and screened, including phenotypes of the leaf, flower, fruit, fiber and plant architecture. Through the plants mutant library, high‐throughput and high‐resolution melting technology‐based variation evaluation detected the EMS‐induced site mutation. Additionally, based on overall genome‐wide mutation analyses by re‐sequencing and mutant library assessment, the examination results demonstrated the ideal quality of the cotton EMS‐treated mutant library constructed in this study with appropriate high mutation density and saturated genome. What is more, the collection is composed of a broad repertoire of mutants, which is the valuable resource for basic genetic research and functional genomics underlying complex allotetraploid traits, as well as cotton breeding. Significance Statement: This study established and verified efficient method/procedure suitable for EMS‐based mutant library construction as the general reference guide in allotetraploid upland cotton. HRM examination and genome‐wide mutation analyses demonstrated ideal quality of the library with appropriate high mutation density and saturated genome. The abundant library is composed of a broad repertoire of mutants as the valuable new resource for basic genetic research and functional genomics underlying complex allotetraploid traits, as well as cotton breeding.